Development of Interactive Articulate Storyline Media to Enhance Learning Interest in Pancasila Education for Fourth-Grade Elementary Students - Junita Dewi Afiyah; Susilo Tri Widodo (AL-ISHLAH: Jurnal Pendidikan, 2025)
Interest in learning Pancasila Education is essential for developing 21st-century competencies such as character and citizenship. However, low student engagement in this subject remains a challenge. Learning media can play a critical role in increasing interest and motivation.This study aimed to develop and evaluate an interactive learning medium using Articulate Storyline to enhance fourth-grade students' interest in Pancasila Education. The research employed a Research and Development (RD) approach using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). Participants included fourth-grade students and teachers from the Ki Hajar Dewantara Elementary School cluster in Semarang, Indonesia. Data collection involved expert validation, student and teacher responses, and pre- and post-tests using learning interest indicators. Statistical analysis included normality, homogeneity, t-tests, and N-Gain tests. The media received a 92% feasibility score from both media and material experts, categorized as "very feasible." Student and teacher responses were also positive, with scores of 87% and 86%, respectively. The t-test yielded a significance value of 0.000, indicating a significant difference in learning interest before and after media use. The N-Gain score was 0.605 (60.5%), categorized as "moderately effective."These results confirm the media’s effectiveness in increasing students’ interest in Pancasila Education by providing interactive, engaging, and accessible content tailored to student characteristics.The Articulate Storyline-based media is feasible and moderately effective for enhancing fourth-grade students’ learning interest in Pancasila Education and is recommended for broader classroom implementation.